2018
DOI: 10.3390/safety4040056
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Methods in Gluten Risk Analysis: A Snapshot

Abstract: Gluten is among the 14 major food allergens officially recognized by Regulation (EU) No. 1169/2011. The risk to coeliac patients from gluten presence in the food products they consume is likely due to the unintentional contamination of naturally gluten-free (GF) and GF-labelled products, or to hidden sources of gluten in processed GF products. The aim of this paper is to provide a snapshot of gluten risk analysis, with emphasis on immunological methods currently used in gluten detection. The study highlights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Moreover, results might be also affected by the number of sampled products and by categories therein. Finally, the cut-off for gluten content in GF products is not harmonized [105]; thus, some products falling under the “gluten-free” category in some countries do not in others.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, results might be also affected by the number of sampled products and by categories therein. Finally, the cut-off for gluten content in GF products is not harmonized [105]; thus, some products falling under the “gluten-free” category in some countries do not in others.…”
Section: Resultsmentioning
confidence: 99%
“…There are several challenges in gluten detection by ELISA methods that have been critically discussed, including the extraction methods, the antibody specificity and detection, and the calibration step with the reference material [ 11 , 12 ]. Using a generic extraction method and a common calibrator, a study revealed that the comparability of all gluten detection commercial kits was very limited [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, the only effective treatment for patients suffering from these pathologies is the complete withdrawal of the harmful ingredient from the diet [ 4 ]. Therefore, the development of methods that allow detection and quantitative determination of the gluten proteins have gained importance in the last decades [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches, including immunodetection, liquid chromatography coupled to mass spectrometry and polymerase chain reaction (PCR)-based methodologies, have been extensively used for the detection of food allergens [ 7 ]. Regarding the detection of gluten, enzyme-linked immunosorbent assay (ELISA) and lateral flow devices have been adopted as official methods to ensure the enforcement of food labelling regulations [ 6 , 8 ]. In this context, the European Union Regulation (EU) No.…”
Section: Introductionmentioning
confidence: 99%